2020
DOI: 10.1021/acs.jafc.9b07621
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Characterization of Aroma Compounds in Silver Carp (Hypophthalmichthys molitrix), Pacific Whiting (Merluccius productus), and Alaska Pollock (Theragra chalcogramma) Surimi by Aroma Extract Dilution Analysis, Odor Activity Value, and Aroma Recombination Studies

Abstract: Aroma compounds in three surimi samples, made from freshwater silver carp (Hypophthalmichthys molitrix) and saltwater Pacific whiting (Merluccius productus) and Alaska pollock (Theragra chalcogramma), were characterized by aroma extract dilution analysis, odor activity value, and odor recombination study. Results demonstrated that the most potent aroma-active compounds in the surimi were hexanal, (Z)-4-heptenal, (Z)-4-decenal, (E,Z)-2,6-nonadienal, (E,E)-2,4-nonadienal, (E,Z)-2,4-decadienal, (E,E)-2,4-decadien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(46 citation statements)
references
References 43 publications
2
44
0
Order By: Relevance
“… Odour description and odour threshold were mainly collected from the following literature and online databases: (An et al. (2020); Fu et al. (2009); Gao et al.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… Odour description and odour threshold were mainly collected from the following literature and online databases: (An et al. (2020); Fu et al. (2009); Gao et al.…”
Section: Resultsmentioning
confidence: 99%
“…a Definitions: MS, mass spectrum (identified thanks to the mass spectra of database); LRI, Linear retention index (compared with the LRI in the literature). b Odour description and odour threshold were mainly collected from the following literature and online databases:(An et al (2020);Fu et al (2009);Gao et al (2020);Giri et al (2010);Gu et al (2013);Jin et al (2018);Ma et al (2020);Selli et al (2006);Varlet et al (2007);Wang et al, 2018;Zhou et al (2016); http://www.flavournet.org; http://www.odour.org.uk).…”
mentioning
confidence: 99%
“…As shown in Figure 6 a, a total of 44 volatile compounds were detected in NT, of which 14 are aldehydes. It has been reported that aldehydes are the main flavor components in surimi products [ 57 , 58 ]. Nonanal, hexanal, heptanal, and valeraldehyde are usually produced by the oxidation of unsaturated fatty acids such as linoleic acid and linolenic acid [ 59 ].…”
Section: Resultsmentioning
confidence: 99%
“…The relative concentrations of volatile compounds in salmon samples were calculated by semiquantitative method (Kesen, 2020) based on the internal standard. Retention indices (RI) were calculated following a modified Kovats method on the basis of the retention times of the external standard n‐alkanes (C 6 ‐C 26 ) under the same GC‐MS detection conditions (, An, Qian, Alcazar MaganaXiong, & Qian, 2020). Identification of detected compounds was performed by comparing the obtained mass spectra with those from Wiley9 and NIST14 libraries, and odor descriptions using the website at http://www.thegoodscentscompany.com.…”
Section: Methodsmentioning
confidence: 99%